Overview Of Risk Factors For Pneumonia In Toddlers At Ibnu Sina Hospital, Makassar, 2022 - Muhammad Rias Sukiman; Muh. Alfian Jafar; Tanty Febriany Takahashi; Destya Maulani; A. Husni Esa Darussalam (Jurnal EduHealth, 2024)
Pneumonia is inflammation that affects the lung parenchyma. Pneumonia is a clinical syndrome, so it is defined based on clinical symptoms and signs, and the course of the disease. Pneumonia is caused by various microorganisms such as bacteria, viruses and fungi. The risk factors for pneumonia are divided into 2, namely intrinsic and extrinsic. To find out the description of the risk factors for pneumonia in toddlers at Ibnu Sina Hospital Makassar in 2022. This research was conducted using a retrospective approach with descriptive methods using secondary data taken from Ibnu Sina Hospital Makassar and analyzed using excel. Sample selection using total sampling of those diagnosed with pneumonia in toddlers with a total sample of 130 toddlers. The highest incidence of pneumonia in toddlers was in males 67 people (52%), aged 13-24 months 36 people (28%), good nutritional status 96 people (74%), received exclusive breastfeeding 86 people (66%), received complete immunization 115 people (89%), no history of air pollution 98 people (75%). Most of the children suffering from pneumonia in toddlers at Ibnu Sina Hospital in Makassar in 2022 were male, most were 12-36 months old, most had good nutritional status, most received exclusive breastfeeding, most did not receive complete immunization and most had no history of pollution. air